Harlequin ichthyosis. - Magaldi, R.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Second born of non consanguineous parents, this boy was born by Cesarean section at the 37th gestational week, with a weight of 2,750 g and height of 51 cm. His skin was completely covered by thick scales, divided by erythematous furrows forming a net outline. There was severe ectropion, so that it was impossible to see the free portion of the upper eyelid. His fingers and toes were deformed and some fingers and toes were shorter (Fig. 1). In the subsequent days the hyperkeratosic scales were gradually eliminated. When aged 15 days he started a galenic preparation of acitretin, at the dosage of 0.5 mg/kg per day, leading to further improvement of the skin lesions and ectropion. The final diagnosis was harlequin ichthyosis. At the age of 5 months (Fig. 2), the clinical features were reminiscent of congenital erythrodermic ichthyosis. Molecular biology was programmed to search for ABCA12 gene mutations.